Targeting the Achievement Gap: Strategies Toward Removing Inequities in Undergraduate Immunology Education - Riestra, Angelica M.; Morales, Abigail J.; Mercer, Frances (Frontiers in Immunology, 2019)
A diverse student body enriches the classroom with lived experiences, varied skillsets, community and cultural knowledge, resiliency, and altruistic interests, all critical attributes that benefit both the classroom and the STEM field at large. However, a persistent disparity in academic and educational attainment exists between under-represented minority (URM) and non-URM students in STEM fields. This achievement gap discourages talented URM students from entering STEM professions, threatening the potential, expertise, and perspective of these professions. Here we describe the factors that contribute to the achievement gap and present strategies, utilized in our Immunology classrooms, for combating each factor. We discuss project-based learning pedagogy to give students increased agency and feelings of empowerment. We also highlight concrete practices to foster students' science identities and sense of community, factors that highly promote STEM retention. The dynamic subject of Immunology provides myriad opportunities to implement a curriculum committed to equity, as we outline below.